Pelatihan Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas Pada Venice Gallery - Sudradjat Sudradjat; Ade Mulyana; Vivi Violandi Grabriela; Kusuma Dewi (Jurnal Abdimas Dedikasi Kesatuan, 2021)
Accounting is often expressed as the language of the company. Accounting systems are forms, records, procedures and tools for processing company data. A good accounting system is needed for every company, one of which is a cash receipt and disbursement system. Cash is one of the assets that has an important role in the development of the company because it is liquid. Based on the results of the study indicate that the accounting information system has an important role in the procedures for cash receipts and disbursements. The accounting information system implemented by Venice Gallery is good and in accordance with company rules. Keywords: Accounting Information System, Accounting, Cash